2019
DOI: 10.3897/zookeys.830.30586
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Marbled Rockfish, Sebastiscus marmoratus (Cuvier, 1829), in the northwestern Pacific Ocean

Abstract: Sebastiscusmarmoratus is an ovoviviparous fish widely distributed in the northwestern Pacific. To examine the gene flow and test larval dispersal strategy of S.marmoratus in Chinese and Japanese coastal waters, 421 specimens were collected from 22 localities across its natural distribution. A 458 base-pair fragment of the mitochondrial DNA (mtDNA) control region was sequenced to examine genetic diversity and population structure. One-hundred-six variable sites defined 166 haplotypes. The populations of S.marmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
4
11
0
Order By: Relevance
“…Meanwhile, populations of SN-KN, which are separated by the South China Sea, showed high genetic connectivity (pairwise F ST = 0.0702). This could probably be explained by the high migration ability of T. jarbua (>1000 km, Liu et al 2015), human-mediated transfer through ballast waters (Liu et al 2019) or past glaciation events. Furthermore, the high similarity in the sequence data (Table 3) perhaps indicates remnants of identical haplotypes from both populations, and that they were essentially similar at one time before the separation (Inger and Chin 2002).…”
Section: Genetic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, populations of SN-KN, which are separated by the South China Sea, showed high genetic connectivity (pairwise F ST = 0.0702). This could probably be explained by the high migration ability of T. jarbua (>1000 km, Liu et al 2015), human-mediated transfer through ballast waters (Liu et al 2019) or past glaciation events. Furthermore, the high similarity in the sequence data (Table 3) perhaps indicates remnants of identical haplotypes from both populations, and that they were essentially similar at one time before the separation (Inger and Chin 2002).…”
Section: Genetic Structurementioning
confidence: 99%
“…A population's genetic structure describes the total genetic diversity in the population, which is shaped by several factors, including the life history, geographical barriers, gene flow, selection and bottlenecks (Wright 1931;Slatkin 1987;Charlesworth 2009;Liu et al 2019). The patterns of genetic diversity and population structure provide information on the life histories, demography, reproduction and ecology of a species.…”
Section: Introductionmentioning
confidence: 99%
“…There are two important indicators to measure the genetic diversity of populations: haplotype and nucleotide (Liu et al, 2006;Song et al, 2014). Nucleotide diversity considers the number of different nucleotides between DNA sequences, so it is often more accurate to reflect the degree of genetic polymorphism in a population than to reflect the genetic distance (Shen et al, 2011;Liu et al, 2019). Overall, high haplotype diversity and nucleotide diversity were found in most populations of S. marmoratus.…”
Section: Discussionmentioning
confidence: 99%
“…Population genetics shows distribution of genetic variability that is affected by natural selection, mutation, migration, population size and genetic drift not only in uenced the genetic variations (Hansen 2003;Xia et al 2014Xia et al , 2015Liu et al 2019) and diversity of the population but was critical to the conservation of species. The genetic variation can be detected by the morphological parameter which was frequently concealed by the environmental factors and infrequency of observable morphological parameters reduced the genetic variability (Hedrick 2005;Mix et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The native extinction was high in small fragmentized populations due to loss of genetic diversity and interruption of genetic drift and inbreeding within and among populations (Maskur 2002;Ruzafa et al 2006;Kahl et al 2008;Syandri et al 2013;Coleman et al 2017). Liu et al (2019) reported that habitat fragmentation is one of the main cause of reduction in biodiversity of aquatic organism like freshwater mussel and dams had adverse effect on aquatic habitat, population genetics and sh communities and other aquatic animals (Cheng et al, 2013;Cheng et al 2018;Morita and Yamamoto 2002;Roberts et al 2013;Terborgh et al, 2001;Wu et al 2003) Ferguson et al (2019 reported the declining of S.trutta (sea trout) due to the presences of barriers such as hydroelectric dams which caused the reproductive and genetic isolation of S.trutta population. Due to the development of PCR technique (Ferguson et al 1995), molecular markers such as SNPs (Single Nucleotide Polymorphism), RAPD (Random Ampli ed Polymorphic DNA) and SSR (Short Sequence repeat or microsatellite) used directly to identify genetic diversity and distribution of the population.…”
Section: Introductionmentioning
confidence: 99%